PENDAPATAN DAN NILAI TAMBAH AGROINDUSTRI GULA KELAPA SKALA RUMAH TANGGA DI KECAMATAN SIDOMULYO KABUPATEN LAMPUNG SELATAN - Puji Arita Lestari; Dwi Haryono; Ktut Murniati (Lampung University, 2020)
The purposes of this research are to analyze the income and added value of household scale coconut sugar agroindustry in Sidomulyo Subdistrict of South Lampung Regency. This research is conducted by a survey method in determining the sample. Respondents are the owners of coconut sugar agroindustries. Data were collected in January - February 2019, and analyzed using quantitative descriptive analysis. The results showed that income over cash costs amounted to Rp2,976,013.89 and income over total costs amounted to Rp529,747.40. Coconut sugar agroindustry was profitable with R/C of 3.66 over cash costs and 1.15 over total costs, it was worth cultivating because it had positive value-added, namely raw material of Rp949.84/ liter. Key words: added value, agroindustry, coconut sugar, income.